2019
DOI: 10.4103/aer.aer_77_19
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided erector spinae plane block compared to modified pectoral plane block for modified radical mastectomy operations

Abstract: Background: Modified radical mastectomy (MRM) is the most common surgery for cancer breast that is associated with marked postoperative pain. Effective control of this pain suppresses the surgical stress response and decreases the opioids and general anesthetics’ needs. This study compared the erector spinae plane (ESP) block and the pectoral plane (PECS) block effects on the opioid consumption postoperatively, stress response, fentanyl needs intraoperatively, pain scores, and incidence of complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 25 publications
5
39
0
Order By: Relevance
“…In the study of Gad et al, pain score and the frequency of analgesics use in the SEP group was higher than in the Pecs group, which was consistent with the results of the present study (16). A clinical trial by Ghamry and Amer (17) aimed at examining the role of erector spinae plane block (ESPB) versus paravertebral block in the control of postoperative pain after mastectomy showed no significant difference in pain score between the two groups within 24 hours (2,4,6).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the study of Gad et al, pain score and the frequency of analgesics use in the SEP group was higher than in the Pecs group, which was consistent with the results of the present study (16). A clinical trial by Ghamry and Amer (17) aimed at examining the role of erector spinae plane block (ESPB) versus paravertebral block in the control of postoperative pain after mastectomy showed no significant difference in pain score between the two groups within 24 hours (2,4,6).…”
Section: Discussionsupporting
confidence: 90%
“…In a study by Altiparmak et al, the mean tramadol dose in the Pecs group was significantly lower than in the ESP group (20). In the study of Gad et al, morphine dose was significantly lower in the Pecs B group than in the ESPB group (16).…”
Section: Discussionmentioning
confidence: 93%
“…Other outcomes reported in the trials comparing erector spinae plane block with pectoralis nerve block included: number of patients requiring postoperative analgesia; time to first rescue analgesia; incidence of injection pain; adverse complications of the blocks; stress hormone levels; and extent of sensory blockade. The number of patients requiring postoperative analgesia was reported in two studies [24, 27] and was significantly higher for the erector spinae plane block group (29 patients (65.9%)) than for pectoralis nerve group (15 patients (34.9%)). Time to first rescue analgesia was recorded by Sinha et al.…”
Section: Resultsmentioning
confidence: 99%
“…Gad et al. [27] measured levels of 'stress hormones' as an outcome and found that there were significant decreases in cortisol and prolactin levels at 1 h and 24 h postoperatively in the pectoralis nerve block group compared with the erector spinae plane block group. Sinha et al.…”
Section: Resultsmentioning
confidence: 99%
“… 80 However, when ESPB was compared with a PECS block, all RCTs demonstrated that the latter led to significantly lower post-operative pain and opioid consumption compared with the former block. 41 , 45 , 52 Finally, only 1 RCT showed that increasing the concertation of bupivacaine from 0.25% to 0.375% led to a further decrease in pain and opioid consumption within the first 24 hours post-surgery.…”
Section: Resultsmentioning
confidence: 99%